Preference-based D2D offloading in IoT-edge-cloud continuum - Chaturvedi, Haripriya; Baranwal, Gaurav (Simulation modelling practice and theory, 2025)
•Device-to-device offloading based on the preferences of IoT and mobile devices.•Inclusion of surcharges based on the offered value of quality parameters.•Maximize the social welfare and number of allocations. Computation tasks are offloaded to the edge server from the Internet of Things (IoT) and mobile devices due to their restricted computation capacity and battery life. However, the fixed capacity of edge servers makes serving multiple IoT and mobile devices challenging for edge servers. The collaborative architecture, i.e. Device-to-Device (D2D)-edge computing, plays a great role in solving this resource gap problem between the IoT and mobile devices and edge servers. The architecture allows the offloading from IoT and mobile devices with restricted resources to IoT and mobile devices with resource-rich resources instead of only edge servers. This collaborative architecture also provides solutions to other edge server-related problems like workload, congestion, bandwidth consumption, and energy consumption along with the utilization of idle resources of nearby IoT and mobile devices. This paper proposes a preference-based D2D offloading model in IoT-Edge-Cloud Continuum. The proposed business model introduces the concept of surcharges to increase the utilization of computing resources. Compared to state-of-the-art work, the model generates more social welfare, increases the number of allocations, and increases participants' utility. With the help of simulation work, we have shown that the work is effective and outperforms.